Tailoring the Adsorptive Efficiency and Pore Characteristics of Silica through Solvothermal Treatment Assisted by Cetyltrimethylammonium Bromide (CTAB) - Timu, Fransiska Altrima Key; Rahman, Nanik Astuti (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
Silica is a porous material widely utilized across various fields. One of the potential sources of silica is sandblasting waste, which contains more than 90% silica. This study aims to investigate the influence of Cetyl Trimethyl Ammonium Bromide (CTAB) concentration and solvothermal duration on producing silica with enhanced adsorption capacity and porosity. The independent variables in this research include CTAB surfactant concentrations of 0.1, 0.2, 0.3, 0.4, and 0.5%, as well as solvothermal processing times of 8, 10, 12, 14, and 16 hours. The optimal result was obtained with the addition of 0.5% CTAB and a solvothermal duration of 16 hours, in which SEM-EDX analysis revealed large visible pores formed by aggregates of fine particles arranged in a homogeneous structure. The adsorption capacity, using a methylene blue concentration of 30 mg, was found to be 27.1822 mg/g. Based on the study on the Enhancement of Adsorption Capacity and Porosity of Silica Using Cetyl Trimethyl Ammonium Bromide (CTAB) via the Solvothermal Method, it can be concluded that both adsorption capacity and porosity are influenced by the addition of CTAB, solvothermal duration, and the concentration of methylene blue used in the adsorption capacity test.